Arthroscopy-assisted partial trapeziectomy combined with ligament reconstruction for thumb carpometacarpal joint osteoarthritis: A different technique - Zheng, Wan-Ling; Wu, Yang-Chun; Shen, Yun-Dong; Yin, Hua-Wei; Xu, Wen-Dong (Frontiers in Surgery, 2022)
Background There is no consensus on the best surgery option for thumb carpometacarpal osteoarthritis (CMC OA). The traditional method has the risk of large trauma, obvious metacarpal subsidence and decreased stability. The aim of this study is to introduce a different technique to restore the function and stability of the first carpal metacarpal joint with minimal trauma, rapid pain relief, reduced complications, and the clinical outcomes in the long term follow-up was evaluated and statistically analyzed. Methods This was a retrospective study of 10 patients with a mean age of 51.8 years. The surgery consisted of removing partial trapezium through arthroscopic, reconstructing the stability with flexor carpi radialis suspension and tendon interposition. The subjective assessment included visual analogue scale (VAS) of pain, quick disabilities of the arm, shoulder, and hand (Quick-DASH) score, and patient satisfaction. The range of motion (ROM), grip strength, pinch strength and radiographic assessment which can reflect stability of the thumb were objectively evaluated and statistically analyzed. Results Ten patients were followed up at a mean follow-up of 6.8 years. The mean grip strength improved significantly from 16.64 kg to 22.57 kg after surgery. Pinch strength improved significantly from 3.72 kg to 5.71 kg on average. The Kapandji score improved signiﬁcantly from 5.7 to 8.6 on average. 80% (8/10) of the patients were satisfied with this surgery. On objective indicators, the VAS score decreased signiﬁcantly from 6.4 to 1.3 on average. The mean Quick-DASH score improved signiﬁcantly from 6.1 to 28.9. Postoperative X-ray showed slight subsidence and dislocation of the first metacarpal in 2 patients, and did not affect the function by measurement. Conclusions Arthroscopic assisted partial trapezium resection combined with ligament reconstruction could be a workable and promising surgical technique in patients with thumb CMC OA. It can offer the advantages of minimizing surgical injury by preserving the first carpal metacarpal joint capsule to protect its stability, with a rapid pain relief, function improvement and satisfactory results in patients’ clinical measurements.